KESENIAN TERBANG MEDAL KERAMAT CEMPAKA MULYA DALAM UPACARA NGARUWAT BUMI DI DESA SUKAMUKTI KECAMATAN MAJALAYA KABUPATEN BANDUNG - Firly Fauzia (SELONDING, 2013)
Kesenian Terbang Medal Keramat Cempaka Mulya, in Sukamukti village, Majalaya subdistrict of Bandung regency, has a special presentation structure that still holding on to the traditions common to the ancestors in organizing the performance ensemble. This musical performance can be categorized as a multifunctional Tambourine ensemble performed not only in religious rituals, but also in other ceremonies for circumcision, wedding, ngaruwat bayi (ritual cleansing and purification for children), or ngaruwat bumi (earth cleansing and purification rituals), and so on. The problem to be studied comprises the function and structure of performance of Kesenian Terbang Medal Keramat Cempaka Mulya in Sukamukti village, Majalaya subdistrict, Bandung regency. The study employed an analytic descriptive method using an ethnomusicological approach. The data were collected through observation, interview, literature review, and documentation. By this method, the author can describe how the Kesenian Terbang Medal Keramat Cempaka Mulya in Sukamukti village, Majalaya subdistrict, Bandung regency performs in Ngaruwat Bumi ceremony. Ngaruwat Bumi ceremony starts with Ijab Qabul (Muslim marriage contract) and Tawasulan (Islamic prayer). In this event, Kesenian Terbang Medal Keramat Cempaka Mulya performs Terbang Buhun. Subsequently, the celebration event was held by involving the community to presents the songs of joy. In this event, Kesenian Terbang Medal Keramat Cempaka Mulya performs Terbang Bangreng and Terbang Akrobat.